A chitosan-crown ether polyimide modified cellulose membrane, a preparation method and application thereof

CN118698512BActive Publication Date: 2026-10-30HENAN ACADEMY OF SCI CHEM RES INST CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410780582.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-17
Publication Date
2026-10-30
Estimated Expiration
2044-06-17

AI Technical Summary

Technical Problem

火法冶金整个过程在高温下完成,产生的能耗过高

Benefits of technology

[0029]与传统利用冠醚制备球形或聚合物吸附材料不同,本发明制备的改性纤维素膜中,冠醚能够暴露在纤维素膜表面,能够有效解决冠醚吸附位点被包覆,无法充分发挥其吸附性能的问题。本发明提供的改性纤维素膜对锂离子的吸附能力有了进一步提高,因此能够从废旧锂电和盐湖资源中选择性回收锂资源,且吸附过程绿色环保。实施例结果表明,本发明提供的壳聚糖-冠醚聚酰亚胺改性纤维素膜比表面积范围为12~50m2/g,对锂的吸附量为20~40mg/g;在干扰离子存在情况下,本发明壳聚糖-冠醚聚酰亚胺改性纤维素膜对其吸附量分别为:锂35mg/g、钠5.5mg/g、钾6.2mg/g、钙7.4mg/g、镁8.6mg/g、锰8.8mg/g,具有较好的选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118698512B_ABST
    Figure CN118698512B_ABST
Patent Text Reader

Abstract

The application provides a chitosan-crown ether polyimide modified cellulose membrane and a preparation method and application thereof, and belongs to the technical field of lithium ion selective adsorption. The application can quickly and controllably prepare the modified cellulose membrane with different crown ether polyimide loadings and high specific surface areas by using surface spin coating and in-situ immobilization technology. In addition, since the crown ether polyimide has the characteristics of selectively adsorbing metal ions, the crown ether polyimide is blended and spin coated on the surface of the cellulose membrane together with chitosan, and a high-performance lithium ion adsorption membrane material can be obtained. Different from the traditional preparation of spherical or polymer adsorption materials by using crown ethers, in the modified cellulose membrane prepared by the application, the crown ethers can be exposed on the surface of the cellulose membrane, and the problem that the adsorption sites of the crown ethers cannot fully play their adsorption performance due to being covered can be effectively solved. The adsorption capacity of the modified cellulose membrane provided by the application for lithium ions is further improved, and therefore, lithium resources can be selectively recovered from waste lithium batteries and salt lake resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion selective adsorption technology, and particularly to a chitosan-crown ether polyimide modified cellulose membrane, its preparation method, and its application. Background Technology

[0002] In recent years, the rapid development of the new energy vehicle manufacturing industry has led to a surge in demand for lithium-ion batteries, resulting in a shortage of high-purity electronic-grade lithium carbonate resources. Simultaneously, due to the limited lifespan of currently used lithium batteries, a large number of waste lithium-ion batteries will be generated in the future. Therefore, the efficient recycling of metallic lithium from waste batteries is of great significance for achieving waste resource recovery and environmental protection. Developing convenient and efficient lithium-ion selective adsorption separation technologies and functional materials is essential for recovering metallic lithium from waste lithium batteries.

[0003] Pyrometallurgy and hydrometallurgy are two main technologies for recovering metal ions in the industrial field. Hydrometallurgical extracts require various techniques for separation and purification to recover lithium resources, involving precipitation, ion exchange, imprinted capacitor deionization, solvent extraction, and electrochemistry. However, these operations are complex, costly, and require significant investment in reagents, energy, and capital. Pyrometallurgy involves removing the battery casing, mixing the battery core with coke and limestone, and then reducing and roasting it to obtain a carbon alloy composed of lithium, cobalt, nickel, aluminum, etc., which is then further processed to recover the lithium component. The entire pyrometallurgical process is completed at high temperatures, resulting in excessive energy consumption.

[0004] Therefore, there is a need to develop a green, environmentally friendly, and efficient method for purifying and recovering lithium ions from large quantities of discarded lithium-ion batteries. Summary of the Invention

[0005] In view of this, the present invention aims to provide a chitosan-crown ether polyimide modified cellulose membrane, its preparation method, and its application. The chitosan-crown ether polyimide modified cellulose membrane prepared by the present invention has a high specific surface area, exhibits excellent adsorption effect on lithium ions, and the adsorption process is green and environmentally friendly.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for preparing a chitosan-crown ether polyimide modified cellulose membrane, comprising the following steps:

[0008] A membrane-modified solution is obtained by mixing crown ether polyimide, an organic solvent, and a chitosan solution.

[0009] Cellulose casting solution was spin-coated into a film, and a film modification solution and glutaraldehyde were sequentially loaded during the film formation process to carry out a crosslinking reaction, thereby obtaining a chitosan-crown ether polyimide modified cellulose membrane precursor.

[0010] NaOH solution was loaded onto the surface of the chitosan-crown ether polyimide modified cellulose membrane precursor and cured to obtain the chitosan-crown ether polyimide modified cellulose membrane.

[0011] Preferably, the crown ether polyimide comprises one or more of dibenzo-12-crown-4 polyimide, dibenzo-14-crown-4 polyimide, dibenzo-15-crown-5 polyimide, and dibenzo-18-crown-6 polyimide;

[0012] The mass ratio of crown ether polyimide to chitosan is 1:0.5 to 1.5.

[0013] Preferably, the crown ether polyimide includes dibenzo-14-crown-4 polyimide and other crown ether polyimide materials, wherein the other crown ether polyimide materials include one of dibenzo-12-crown-4 polyimide, dibenzo-15-crown-5 polyimide and dibenzo-18-crown-6 polyimide;

[0014] The mass ratio of the dibenzo-14-crown-4 polyimide to other crown ether polyimide materials is 1 to 3:1.

[0015] Preferably, the organic solvent includes a first solvent and a second solvent, wherein the first solvent includes one of N,N'-dimethylformamide, N,N'-dimethylacetamide and N-methylpyrrolidone, and the second solvent includes acetone or acetonitrile;

[0016] The mass ratio of the crown ether polyimide to the volume ratio of the solvent is 1 g: 8-15 mL.

[0017] Preferably, the cellulose casting solution comprises cellulose powder and a solvent, wherein the mass concentration of cellulose powder in the cellulose casting solution is 6-10%.

[0018] The cellulose membrane obtained after the cellulose casting solution is used to form a film has a pore size of 0.25–0.45 μm.

[0019] Preferably, the volume ratio of the membrane modification solution to the cellulose casting solution is 0.2 to 0.5:1;

[0020] The volume ratio of the membrane modification solution to glutaraldehyde is 50–200: 20–50;

[0021] The cross-linking reaction takes 3 to 10 minutes.

[0022] Preferably, the concentration of the NaOH solution is 0.7–1.4 mol / L;

[0023] The volume ratio of the membrane modification solution to the NaOH solution is 50-200:500-1000;

[0024] The curing time is 10 to 15 minutes.

[0025] The present invention provides a chitosan-crown ether polyimide modified cellulose membrane prepared by the above preparation method, comprising a cellulose membrane and chitosan and crown ether polyimide loaded on the surface and internal pores of the cellulose membrane.

[0026] Preferably, the chitosan-crown ether polyimide modified cellulose membrane has a specific surface area of ​​12–50 m². 2 / g.

[0027] This invention provides the application of the above-mentioned chitosan-crown ether polyimide modified cellulose membrane in the adsorption of lithium ions.

[0028] This invention provides a method for preparing a chitosan-crown ether polyimide-modified cellulose membrane, comprising the following steps: mixing crown ether polyimide, an organic solvent, and a chitosan solution to obtain a membrane modification solution; spin-coating a cellulose casting solution into a membrane, sequentially loading the membrane modification solution and glutaraldehyde during the membrane formation process to perform a crosslinking reaction, thereby obtaining a chitosan-crown ether polyimide-modified cellulose membrane precursor; loading a NaOH solution onto the surface of the chitosan-crown ether polyimide-modified cellulose membrane precursor and curing it to obtain the chitosan-crown ether polyimide-modified cellulose membrane. This invention utilizes surface spin-coating and in-situ immobilization technology to rapidly and controllably prepare modified cellulose membranes with different crown ether polyimide loadings and high specific surface areas. Furthermore, since crown ether polyimide has the characteristic of selectively adsorbing metal ions, its blending with chitosan and spin-coating onto the surface of a cellulose membrane can yield a high-performance lithium-ion adsorption membrane material. When chitosan is spin-coated, it can crosslink with crown ether polyimide to form a network-like structure, which, together with cellulose, forms the backbone of the membrane material. After crosslinking and curing, a rigid network backbone is formed, within which the crown ether polyimide is confined and fixed. The crown ether polyimide confined by the chitosan / cellulose backbone is not dissolved by water / acid during regeneration through lithium ion adsorption or desorption in water, thus preventing material loss and enabling material reuse.

[0029] Unlike traditional methods of preparing spherical or polymeric adsorbent materials using crown ethers, the modified cellulose membrane prepared in this invention exposes the crown ether on the membrane surface, effectively solving the problem of crown ether adsorption sites being coated and unable to fully utilize their adsorption performance. The modified cellulose membrane provided by this invention further improves the adsorption capacity for lithium ions, thus enabling selective recovery of lithium resources from waste lithium batteries and salt lake resources, and the adsorption process is green and environmentally friendly. The results of the examples show that the chitosan-crown ether polyimide modified cellulose membrane provided by this invention has a specific surface area ranging from 12 to 50 m². 2The adsorption capacity for lithium is 20-40 mg / g. In the presence of interfering ions, the adsorption capacities of the chitosan-crown ether polyimide modified cellulose membrane of the present invention are: lithium 35 mg / g, sodium 5.5 mg / g, potassium 6.2 mg / g, calcium 7.4 mg / g, magnesium 8.6 mg / g, and manganese 8.8 mg / g, respectively, showing good selectivity.

[0030] Meanwhile, the preparation method provided by this invention is simple to operate, low in cost, and easy to achieve industrial-scale mass production. Attached Figure Description

[0031] Figure 1 This is a scanning electron microscope image of the chitosan-crown ether polyimide modified cellulose membrane obtained in Example 1;

[0032] Figure 2 The image shows a scanning electron microscope image of the chitosan-modified cellulose membrane obtained in Comparative Example 1.

[0033] Figure 3 This is a scanning electron microscope image of the dibenzo-14-crown-4 polyimide modified cellulose membrane obtained in Comparative Example 2. Detailed Implementation

[0034] This invention provides a method for preparing a chitosan-crown ether polyimide modified cellulose membrane, comprising the following steps:

[0035] A membrane-modified solution is obtained by mixing crown ether polyimide, an organic solvent, and a chitosan solution.

[0036] Cellulose casting solution was spin-coated into a film, and a film modification solution and glutaraldehyde were sequentially loaded during the film formation process to carry out a crosslinking reaction, thereby obtaining a chitosan-crown ether polyimide modified cellulose membrane precursor.

[0037] NaOH solution was loaded onto the surface of the chitosan-crown ether polyimide modified cellulose membrane precursor and cured to obtain the chitosan-crown ether polyimide modified cellulose membrane.

[0038] Unless otherwise specified, all raw materials used in this invention are commercially available.

[0039] This invention involves mixing crown ether polyimide, an organic solvent, and a chitosan solution to obtain a membrane-modified solution. In this invention, the molecular weight of the crown ether polyimide is preferably 200–6000, more preferably 1000–5200, and even more preferably 2000–4500. In this invention, the crown ether polyimide preferably includes one or more of dibenzo-12-crown-4 polyimide, dibenzo-14-crown-4 polyimide, dibenzo-15-crown-5 polyimide, and dibenzo-18-crown-6 polyimide. More preferably, the crown ether polyimide is dibenzo-14-crown-4 polyimide, and the dibenzo-14-crown-4 polyimide material exhibits the best lithium-ion binding effect.

[0040] Alternatively, the crown ether polyimide includes dibenzo-14-crown-4 polyimide and other crown ether polyimide materials, wherein the other crown ether polyimide materials include one of dibenzo-12-crown-4 polyimide, dibenzo-15-crown-5 polyimide, and dibenzo-18-crown-6 polyimide; the mass ratio of the dibenzo-14-crown-4 polyimide to other crown ether polyimide materials is preferably 1 to 3:1, more preferably 2:1.

[0041] This invention does not impose any special requirements on the preparation method of the crown ether polyimide; any crown ether polyimide preparation method well known to those skilled in the art can be used. As a specific embodiment of this invention, the preparation method of the dibenzo-14-crown-4 polyimide refers to patent CN202210041767.3, "A Preparation Method of Dibenzo-14-crown-4 Polyamide for Lithium Extraction from Salt Lakes"; the preparation method of the dibenzo-15-crown-5 polyimide refers to: Sun Y, Zhu M, Yao Y, et al. "A Novel Approach for the Selective Extraction of Li+ from the Leaching Solution of Spent Lithium-ion Batteries Using benzo-15-crown-5ether as..." extractant[J]. Elsevier, 2020. DOI:10.1016 / j.seppur.2019.116325; The preparation method of the dibenzo-18-crown-6 polyimide is referenced in: Yang Ting. Preparation and performance study of dibenzo-18-crown-6 polyimide[D]. Jiangxi Normal University [2024-06-03]. DOI:CNKI:CDMD:2.1018.135737.

[0042] In this invention, the molecular weight of the chitosan is preferably 50-90 kDa, more preferably 55-80 kDa; the chitosan solution is preferably a chitosan glacial acetic acid solution, and the volume concentration of the glacial acetic acid is preferably 0.5-1.5%, more preferably 1%. The mass ratio of the chitosan to the volume ratio of the glacial acetic acid is preferably 0.5-1.5 g: 80-100 mL, more preferably 1 g: 80-100 mL.

[0043] In this invention, the method for preparing the chitosan solution preferably includes the following steps:

[0044] Chitosan and glacial acetic acid were stirred and mixed to obtain a chitosan solution.

[0045] In this invention, the stirring and mixing is preferably done using magnetic stirring, and the stirring speed is preferably 500-1000 rpm, more preferably 600-800 rpm; the stirring time is preferably 15-30 min, more preferably 20-25 min. Through magnetic stirring, this invention ensures that chitosan is fully dissolved, obtaining a uniform, bubble-free, pale yellow chitosan solution.

[0046] In this invention, the mass ratio of the crown ether polyimide to the chitosan in the chitosan solution is preferably 1:0.5 to 1.5, more preferably 1:0.8 to 1.2.

[0047] In this invention, the organic solvent preferably includes a first solvent and a second solvent. The first solvent preferably includes one of N,N'-dimethylformamide, N,N'-dimethylacetamide, and N-methylpyrrolidone, and the second solvent preferably includes acetone or acetonitrile. In this invention, the volume ratio of the first solvent to the second solvent is preferably 1:5 to 8, more preferably 1:6 to 7. In this invention, the organic solvent is well miscible with water, facilitating the loading of crown ether polyimide onto chitosan. Simultaneously, the organic solvent used in this invention is easily volatile, allowing the material to be efficiently and uniformly dispersed on the membrane material surface during spin coating. The evaporation process makes the cellulose membrane porous, which helps increase the contact area between the material and the lithium-containing aqueous sample, allowing the lithium-containing aqueous sample to flow quickly through the membrane material. In this invention, the mass ratio of the crown ether polyimide to the volume ratio of the solvent is preferably 1g:8 to 15mL, more preferably 1g:10 to 12mL.

[0048] In this invention, the mixing method of the crown ether polyimide, organic solvent, and chitosan solution preferably includes the following steps:

[0049] First, the crown ether polyimide is mixed with an organic solvent, and then the mixture is mixed with a chitosan solution.

[0050] In this invention, the first mixing method is preferably stirring, and more preferably magnetic stirring. The stirring speed is preferably 400–800 rpm, and more preferably 500–600 rpm; the stirring time is preferably 5–20 min, and more preferably 10–15 min. Through this stirring, the crown ether polyimide and the organic solvent are thoroughly and uniformly mixed without bubbles.

[0051] In this invention, the volume ratio of the mixture to the chitosan solution is preferably 1:3 to 10, more preferably 1:5 to 8. In this invention, the second mixing is preferably stirred, more preferably magnetically stirred; the stirring speed is preferably 500 to 1000 rpm, more preferably 600 to 800 rpm; the stirring time is preferably 15 to 30 minutes, more preferably 20 to 25 minutes.

[0052] This invention involves spin-coating a cellulose casting solution into a film. During the film formation process, a film modification solution and glutaraldehyde are sequentially loaded to undergo a crosslinking reaction, yielding a chitosan-crown ether polyimide-modified cellulose membrane precursor. In this invention, the cellulose casting solution preferably comprises cellulose powder and a solvent. The cellulose powder preferably has a particle size of 20–40 μm, more preferably 25–30 μm.

[0053] In this invention, the solvent is preferably a mixed solution of 1-ethyl-3-methylimidazolium acetate and acetonitrile, and the volume ratio of 1-ethyl-3-methylimidazolium acetate to acetonitrile in the solvent is preferably 4 to 5:1.

[0054] In this invention, the mass concentration of cellulose powder in the cellulose casting solution is preferably 6-10%, more preferably 7-9%.

[0055] In this invention, the pore size of the cellulose membrane obtained after the cellulose casting solution is formed is preferably 0.25-0.45 μm, more preferably 0.3-0.4 μm, and the membrane diameter is preferably 13-50 mm, more preferably 20-40 mm.

[0056] The present invention preferably uses a spin coater to perform the spin coating film formation. In the present invention, the spin coating film formation speed is preferably 200-500 rpm, more preferably 300-400 rpm.

[0057] In this invention, the preferred method for loading the membrane modification solution is dropwise addition, more preferably pipette addition or syringe addition. When using a pipette for addition, the pipette is preferably equipped with a 200 μL tip, and the distance between the tip and the membrane surface is preferably 1–5 cm, more preferably 2–4 cm. When using a syringe for addition, a syringe pump is preferably used, and the addition rate is preferably 3–8 mL / min, more preferably 5–6 mL / min.

[0058] In this invention, the volume ratio of the membrane modification solution to the cellulose casting solution is preferably 0.2–0.5:1, more preferably 0.3–0.4:1. In this invention, the membrane modification solution is preferably loaded at the center of the cellulose membrane.

[0059] In this invention, the preferred loading method for glutaraldehyde is dropwise addition. In this invention, the preferred volume ratio of the membrane modification solution to glutaraldehyde is 50–200:20–50, more preferably 100–150:30–40. In this invention, the spin-coating speed remains constant during the loading process of the membrane modification solution and glutaraldehyde.

[0060] In this invention, the crosslinking reaction is preferably carried out at room temperature and for 3 to 10 minutes, more preferably 4 to 6 minutes. During the crosslinking reaction, the hydroxyl, amino, and amide groups on chitosan react with the hydroxyl groups on cellulose under the action of glutaraldehyde to form a network structure with a rigid framework.

[0061] After obtaining the chitosan-crown ether polyimide modified cellulose membrane precursor, the present invention loads NaOH solution onto the surface of the chitosan-crown ether polyimide modified cellulose membrane precursor and cures it to obtain the chitosan-crown ether polyimide modified cellulose membrane. In the present invention, the concentration of the NaOH solution is preferably 0.7-1.4 mol / L, more preferably 1 mol / L; the volume ratio of the membrane modification solution to the NaOH solution is preferably 50-200:500-1000, more preferably 150-200:600-800. In the present invention, the curing temperature is preferably room temperature, and the time is preferably 10-15 minutes, more preferably 12-14 minutes. Through the curing process, the present invention can neutralize the acetic acid used in the early stage, so that the membrane material is in an alkaline environment. Under such conditions, the hydroxyl and amino groups on chitosan and cellulose will react with sodium hydroxide to form more stable salts, further improving the rigid framework and stability of the material.

[0062] After curing, the resulting chitosan-crown ether polyimide modified cellulose membrane is preferably washed and dried. In this invention, the washing solution is preferably deionized water, and the washing is preferably performed three times. Through this washing process, residual organic solvents, glacial acetic acid, NaOH, and other substances are removed.

[0063] In this invention, the drying temperature is preferably 25-45°C, more preferably 30-40°C; the drying time is preferably 40-70 min, more preferably 50-60 min.

[0064] This invention utilizes cellulose membrane as the parent material and proposes a method for rapid surface modification of membrane materials. This method is simple and efficient, avoids the problem of loss of adsorption sites caused by preparing spherical adsorbent materials with crown ether polyimide, and the prepared membrane material has good selective adsorption performance for lithium.

[0065] The present invention provides a chitosan-crown ether polyimide modified cellulose membrane prepared by the above preparation method, comprising a cellulose membrane and chitosan and crown ether polyimide loaded on the surface and internal pores of the cellulose membrane.

[0066] In this invention, the specific surface area of ​​the chitosan-crown ether polyimide modified cellulose membrane is preferably 12-50 m². 2 / g, more preferably 20-40m 2 / g; pore size is preferably 200-500nm, more preferably 300-400nm; porosity is preferably 47-68%, more preferably 50-64%.

[0067] In this invention, the adsorption capacity of the chitosan-crown ether polyimide modified cellulose membrane for lithium is preferably 20-40 mg / g, more preferably 25-35 mg / g.

[0068] This invention provides the application of the chitosan-crown ether polyimide modified cellulose membrane in the adsorption of lithium ions. In this invention, the application preferably includes the extraction of lithium ions from salt lake brine or the recovery of metallic lithium from spent lithium batteries.

[0069] In this invention, the method of application preferably includes the following steps:

[0070] A lithium-containing water sample was passed through a chitosan-crown ether polyimide modified cellulose membrane to adsorb lithium ions.

[0071] In this invention, the concentration of lithium ions in the lithium-containing water sample is preferably 10–500 mg / L, more preferably 60–400 mg / L, and even more preferably 100–300 mg / L. In this invention, the flow rate of the lithium-containing water sample is preferably 1–8 L / min, more preferably 2–5 L / min.

[0072] The following detailed description, in conjunction with embodiments, illustrates the chitosan-crown ether polyimide modified cellulose membrane, its preparation method, and its applications provided by the present invention. However, these descriptions should not be construed as limiting the scope of protection of the present invention.

[0073] Example 1

[0074] (1) Weigh 1g of dibenzo-12-crown-4 polyimide.

[0075] (2) The solvent used is a mixed solvent: N,N'-dimethylformamide + acetone, with a volume ratio of 1:6.

[0076] (3) Mix material (1) with solvent (2) to obtain a ratio of 1g:8mL. During mixing, add the two solutions to a reaction vessel with magnetic stirring and stir continuously at 600rpm for 15min to ensure that they are fully mixed and free of bubbles, thus obtaining a mixed sample.

[0077] (4) Take 1g of chitosan and dissolve it in a 1% glacial acetic acid solution with a volume of 90mL. Then place it in a container with a magnetic stirrer and stir continuously at 700rpm for 20min to fully dissolve the chitosan and obtain a uniform, bubble-free, light yellow chitosan solution.

[0078] (5) Dissolve the mixed sample in chitosan solution at a volume ratio of 1:6. After mixing, place the mixture in a container with a magnetic stirrer and stir continuously at 600 rpm for 16 min to obtain a membrane modification solution, which can be used for subsequent spin coating on the membrane surface.

[0079] (6) Cellulose powder with a particle size of 25 μm was dissolved in a mixed solution of 1-ethyl-3-methylimidazolium acetate and acetonitrile (volume ratio 4.4:1), with a cellulose powder mass fraction of 8%, to obtain a cellulose casting solution. The casting solution was then spin-coated using a spin coater at a speed of 300 rpm to obtain a cellulose membrane with a pore size of 0.25 μm and a membrane diameter of 40 mm. Simultaneously, 120 μL of membrane modification solution was dropped onto the center of the membrane. During the drop-off, a pipette with a 200 μL tip was used, with the tip 1 cm away from the membrane surface. After the addition was complete, while maintaining the same speed, 35 μL of glutaraldehyde solution was added for crosslinking. Then, 600 μL of 1 mol / L NaOH solution was added for secondary curing. Finally, 5 mL of deionized water was added three times to rinse the membrane surface to remove residual organic solvents, glacial acetic acid, NaOH, and other substances. The membrane material was then dried at 32°C for 55 min to obtain a chitosan-crown ether polyimide modified cellulose membrane. The obtained chitosan-crown ether polyimide modified cellulose membrane had a pore size of 435 nm and a porosity of 67%.

[0080] The scanning electron microscope image of the chitosan-crown ether polyimide modified cellulose membrane obtained in Example 1 is shown below. Figure 1 As shown in the figure, scanning electron microscopy observation of the membrane surface morphology reveals that the cellulose membrane material itself has a loose and porous structure, with channels formed between the fibers allowing the solution to flow easily through the membrane. The fiber surface is relatively smooth. In contrast, the modified membrane material exhibits a rough, granular structure, which is due to the modification with chitosan and crown ether polyimide. This indicates that the modified cellulose membrane material prepared by this method has a larger specific surface area and increased adsorption sites, which is beneficial for the efficient adsorption of lithium ions in water.

[0081] The specific testing method for the dynamic cyclic adsorption experiment is as follows: The membrane is placed in a membrane cell with an effective diameter of 10 mm, and a lithium chloride solution with a concentration of 300 mg / L is used. The membrane's effect on Li₂ is studied over an operating time of 3 hours. + The adsorption performance of Li was determined by ICP-OES. + The equilibrium adsorption capacity for lithium ions can be obtained from the solution concentration.

[0082] The maximum adsorption capacity of the chitosan-crown ether polyimide modified cellulose membrane obtained in Example 1 was 37 mg / g, as determined by dynamic cyclic adsorption experiments.

[0083] Example 2

[0084] (1) Weigh 1g of a mixture of dibenzo-12-crown-4 polyimide and dibenzo-14-crown-4 polyimide, with a molar ratio of 1:1.

[0085] (2) The solvent used is a mixed solvent: N,N'-dimethylacetamide + acetone, with a volume ratio of 1:7.

[0086] (3) Mix material (1) with solvent (2) in a ratio of 1g:10mL. When mixing, add the two solutions to a reaction vessel with a magnetic stirrer and stir continuously at 700rpm for 12min to ensure that they are fully mixed and free of bubbles, thus obtaining a mixed sample.

[0087] (4) Take 1.2g of chitosan and dissolve it in a 1.1% glacial acetic acid solution with a volume of 90mL. Then place it in a container with a magnetic stirrer and stir continuously at 700rpm for 20min to fully dissolve the chitosan and obtain a uniform, bubble-free, light yellow chitosan solution.

[0088] (5) Dissolve the mixed sample in chitosan solution at a volume ratio of 1:6. After mixing, place the mixture in a container with a magnetic stirrer and stir continuously at 600 rpm for 20 min to obtain a membrane modification solution, which can be used for subsequent spin coating on the membrane surface.

[0089] (6) Cellulose powder with a particle size of 25 μm was dissolved in a mixed solution of 1-ethyl-3-methylimidazolium acetate and acetonitrile (volume ratio 4.4:1), with a cellulose powder mass fraction of 8%, to obtain a cellulose casting solution. The casting solution was then spin-coated using a spin coater at a speed of 300 rpm to obtain a cellulose membrane with a pore size of 0.25 μm and a membrane diameter of 40 mm. Simultaneously, 100 μL of membrane modification solution was dropped onto the center of the membrane. During the drop-off, a pipette with a 200 μL tip was used, with the tip 1 cm away from the membrane surface. After the addition was complete, while maintaining the same speed, 30 μL of glutaraldehyde solution was added for crosslinking. Then, 600 μL of 1 mol / L NaOH solution was added for secondary curing. Finally, 5 mL of deionized water was added three times to rinse the membrane surface to remove residual organic solvents, glacial acetic acid, NaOH, and other substances. The membrane material was then dried at 35°C for 50 min to obtain a chitosan-crown ether polyimide modified cellulose membrane. The obtained chitosan-crown ether polyimide modified cellulose membrane had a pore size of 426 nm and a porosity of 65%.

[0090] A dynamic cyclic adsorption experiment was conducted according to the method in Example 1. The maximum adsorption capacity of the chitosan-crown ether polyimide modified cellulose membrane obtained in Example 2 for lithium ions was 32 mg / g, as determined by the dynamic cyclic adsorption experiment.

[0091] Example 3

[0092] (1) Weigh 1g of a mixture of dibenzo-14-crown-4 polyimide and dibenzo-18-crown-6 polyimide, with a molar ratio of 3:1.

[0093] (2) The solvent used is a mixed solvent: N-methylpyrrolidone + acetonitrile, with a volume ratio of 1:8.

[0094] (3) Mix material (1) with solvent (2) in a ratio of 1g:10mL. When mixing, add the two solutions to a reaction vessel with a magnetic stirrer and stir continuously at 700rpm for 15min to ensure that they are fully mixed and free of bubbles, thus obtaining a mixed sample.

[0095] (4) Take 0.8g of chitosan and dissolve it in a 1.3% glacial acetic acid solution with a volume of 80mL. Then place it in a container with a magnetic stirrer and stir continuously at 600rpm for 20min to fully dissolve the chitosan and obtain a uniform, bubble-free, light yellow chitosan solution.

[0096] (5) Dissolve the mixed sample in chitosan solution at a volume ratio of 1:6. After mixing, place the mixture in a container with a magnetic stirrer and stir continuously at 500 rpm for 20 min to obtain a membrane modification solution, which can be used for subsequent spin coating on the membrane surface.

[0097] (6) Cellulose powder with a particle size of 25 μm was dissolved in a mixed solution of 1-ethyl-3-methylimidazolium acetate and acetonitrile (volume ratio 4.4:1), with a cellulose powder mass fraction of 8%, to obtain a cellulose casting solution. The casting solution was then spin-coated using a spin coater at a speed of 400 rpm to obtain a cellulose membrane with a pore size of 0.45 μm and a membrane diameter of 40 mm. Simultaneously, 180 μL of membrane modification solution was dropped onto the center of the membrane. During the drop-off, a pipette with a 200 μL tip was used, with the tip 2 cm away from the membrane surface. After the addition was complete, 45 μL of glutaraldehyde solution was added dropwise while maintaining the rotation speed to crosslink the membrane. Then, 800 μL of 1 mol / L NaOH solution was added dropwise for secondary curing. Finally, 8 mL of deionized water was added three times to rinse the membrane surface to remove residual organic solvents, glacial acetic acid, NaOH, and other substances. The membrane material was then dried at 40°C for 55 min to obtain a chitosan-crown ether polyimide modified cellulose membrane. The obtained chitosan-crown ether polyimide modified cellulose membrane had a pore size of 430 nm and a porosity of 66%.

[0098] A dynamic cyclic adsorption experiment was conducted according to the method in Example 1. The maximum adsorption capacity of the chitosan-crown ether polyimide modified cellulose membrane obtained in Example 3 for lithium ions was 28 mg / g, as determined by the dynamic cyclic adsorption experiment.

[0099] Example 4

[0100] (1) Weigh 1g of a mixture of dibenzo-14-crown-4 polyimide and dibenzo-15-crown-5 polyimide, with a molar ratio of 2:1.

[0101] (2) The solvent used is a mixed solvent: N,N'-dimethylformamide + acetonitrile, with a volume ratio of 1:8.

[0102] (3) Mix material (1) with solvent (2) in a ratio of 1g:12mL. When mixing, add the two solutions to a reaction vessel with a magnetic stirrer and stir continuously at 400rpm for 12min to ensure that they are fully mixed and free of bubbles, thus obtaining a mixed sample.

[0103] (4) Take 1.2g of chitosan and dissolve it in a 1.4% glacial acetic acid solution with a volume of 86mL. Then place it in a container with a magnetic stirrer and stir continuously at 550rpm for 15min to fully dissolve the chitosan and obtain a uniform, bubble-free, light yellow chitosan solution.

[0104] (5) Dissolve the mixed sample in chitosan solution at a volume ratio of 1:7. After mixing, place the mixture in a container with a magnetic stirrer and stir continuously at 860 rpm for 24 min to obtain a membrane modification solution, which can be used for subsequent spin coating on the membrane surface.

[0105] (6) Cellulose powder with a particle size of 25 μm was dissolved in a mixed solution of 1-ethyl-3-methylimidazolium acetate and acetonitrile (volume ratio 4.4:1), with a cellulose powder mass fraction of 8%, to obtain a cellulose casting solution. The casting solution was then spin-coated using a spin coater at a speed of 300 rpm to obtain a cellulose membrane with a pore size of 0.45 μm and a membrane diameter of 13 mm. Simultaneously, 100 μL of membrane modification solution was dropped onto the center of the membrane. During the drop-off, a pipette with a 200 μL tip was used, with the tip 1 cm away from the membrane surface. After the addition was complete, while maintaining the same speed, 20 μL of glutaraldehyde solution was added for crosslinking. Then, 500 μL of 1 mol / L NaOH solution was added for secondary curing. Finally, 3 mL of deionized water was added three times to rinse the membrane surface to remove residual organic solvents, glacial acetic acid, NaOH, and other substances. The membrane material was then dried at 25°C for 40 min to obtain a chitosan-crown ether polyimide modified cellulose membrane. The obtained chitosan-crown ether polyimide modified cellulose membrane had a pore size of 435 nm and a porosity of 69%.

[0106] Comparative Example 1

[0107] (1) The solvent used is a mixed solvent: N,N'-dimethylformamide + acetone, with a volume ratio of 1:6.

[0108] (2) Take 1g of chitosan and dissolve it in a 1% glacial acetic acid solution with a volume of 90mL. Then place it in a container with a magnetic stirrer and stir continuously at 700rpm for 20min to fully dissolve the chitosan and obtain a uniform, bubble-free, light yellow chitosan solution.

[0109] (3) Dissolve the mixed solvent (1) in the chitosan solution (2) at a volume ratio of 1:6. After mixing the two, place them in a container with a magnetic stirrer and stir continuously at 600 rpm for 16 min to obtain a membrane modification solution, which is used for subsequent spin coating on the membrane surface.

[0110] (4) Cellulose powder with a particle size of 25 μm was dissolved in a mixed solution of 1-ethyl-3-methylimidazolium acetate and acetonitrile (volume ratio 4.4:1), with a cellulose powder mass fraction of 8%, to obtain a cellulose casting solution. The casting solution was then spin-coated using a spin coater at a speed of 300 rpm to obtain a cellulose membrane with a pore size of 0.25 μm and a membrane diameter of 40 mm. Simultaneously, 120 μL of membrane modification solution was dropped onto the center of the membrane. During the drop-in, a pipette with a 200 μL tip was used, with the tip 1 cm away from the membrane surface. After the addition was complete, 35 μL of glutaraldehyde solution was added dropwise while maintaining the rotation speed to crosslink the membrane. Then, 600 μL of 1 mol / L NaOH solution was added dropwise for secondary curing. Finally, 5 mL of deionized water was added three times to rinse the membrane surface to remove residual organic solvents, glacial acetic acid, NaOH, and other substances. The membrane material was then dried at 32 °C for 55 min to obtain a chitosan-modified cellulose membrane. The obtained chitosan-modified cellulose membrane had a pore size of 440 nm and a porosity of 66%. A scanning electron microscope image of the obtained chitosan-modified cellulose membrane is shown below. Figure 2 As shown.

[0111] A dynamic cyclic adsorption experiment was conducted according to the method in Example 1. The maximum adsorption capacity of the chitosan-modified cellulose membrane obtained in Comparative Example 1 for lithium ions was found to be 8 mg / g.

[0112] The comparison shows that when only chitosan is used, without adsorbent materials such as dibenzo-14-crown-4 polyimide, although the roughness of the membrane is improved as observed by electron microscopy, no effective adsorption sites are formed, and lithium ions cannot be effectively adsorbed. Compared with the examples, the adsorption capacity of the modified membrane material for lithium is significantly reduced.

[0113] Comparative Example 2

[0114] (1) Weigh 1g of dibenzo-14-crown-4 polyimide.

[0115] (2) The solvent used is a mixed solvent: N,N'-dimethylacetamide + acetone, with a volume ratio of 1:7.

[0116] (3) Mix material (1) with solvent (2) in a ratio of 1g:10mL. When mixing, add the two solutions to a reaction vessel with a magnetic stirrer and stir continuously at 700rpm for 12min to ensure that they are fully mixed and free of bubbles, thus obtaining a mixed sample.

[0117] (4) Prepare a 1.1% glacial acetic acid solution.

[0118] (5) Dissolve the mixed sample in glacial acetic acid solution at a volume ratio of 1:6. After mixing, place the mixture in a container with a magnetic stirrer and stir continuously at 600 rpm for 20 min to obtain a membrane modification solution, which can be used for subsequent spin coating on the membrane surface.

[0119] (6) Cellulose powder with a particle size of 25 μm was dissolved in a mixed solution of 1-ethyl-3-methylimidazolium acetate and acetonitrile (volume ratio 4.4:1), with a cellulose powder mass fraction of 8%, to obtain a cellulose casting solution. The casting solution was then spin-coated using a spin coater at a speed of 300 rpm to obtain a cellulose membrane with a pore size of 0.25 μm and a membrane diameter of 40 mm. Simultaneously, 100 μL of membrane modification solution was dropped onto the center of the membrane. During the drop-off, a pipette with a 200 μL tip was used, with the tip 1 cm away from the membrane surface. After the addition was complete, while maintaining the same speed, 30 μL of glutaraldehyde solution was added for crosslinking. Then, 600 μL of 1 mol / L NaOH solution was added for secondary curing. Finally, 5 mL of deionized water was added three times to rinse the membrane surface to remove residual organic solvents, glacial acetic acid, NaOH, etc. The membrane material was then dried at 35°C for 50 min to obtain a dibenzo-14-crown-4 polyimide-modified cellulose membrane. The obtained dibenzo-14-crown-4 polyimide-modified cellulose membrane had a pore size of 450 nm and a porosity of 70%. A scanning electron microscope image of the obtained dibenzo-14-crown-4 polyimide-modified cellulose membrane is shown below. Figure 3 As shown.

[0120] A dynamic cyclic adsorption experiment was conducted according to the method in Example 1. The maximum adsorption capacity of the dibenzo-14-crown-4 polyimide modified cellulose membrane obtained in Comparative Example 2 for lithium ions was 6 mg / g, as determined by the dynamic cyclic adsorption experiment.

[0121] The comparison shows that when only dibenzo-14-crown-4 polyimide is used for immobilization without chitosan as a modified crosslinking material, the material is difficult to retain on the membrane surface, thus hindering the improvement of lithium adsorption performance. Compared to Example 1, the membrane material prepared in Comparative Example 2, although having similar porosity, has a smoother surface, making it difficult to effectively fix the material on the membrane surface. The number of adsorption sites on the material surface is not significantly increased, resulting in poor lithium adsorption performance.

[0122] Comparative Example 3

[0123] (1) Weigh 1g of a mixture of dibenzo-14-crown-4 polyimide and dibenzo-15-crown-5 polyimide, with a molar ratio of 2:1.

[0124] (2) The solvent used is a mixed solvent: N,N'-dimethylformamide + acetonitrile, with a volume ratio of 1:8.

[0125] (3) Mix material (1) with solvent (2) in a ratio of 1g:12mL. When mixing, add the two solutions to a reaction vessel with a magnetic stirrer and stir continuously at 400rpm for 12min to ensure that they are fully mixed and free of bubbles, thus obtaining a mixed sample.

[0126] (4) Take 1.2g of chitosan and dissolve it in a 1.4% glacial acetic acid solution with a volume of 86mL. Then place it in a container with a magnetic stirrer and stir continuously at 550rpm for 15min to fully dissolve the chitosan and obtain a uniform, bubble-free, light yellow chitosan solution.

[0127] (5) Dissolve the mixed sample in chitosan solution at a volume ratio of 1:7. After mixing, place the mixture in a container with a magnetic stirrer and stir continuously at 860 rpm for 24 min to obtain a membrane modification solution, which can be used for subsequent spin coating on the membrane surface.

[0128] (6) Cellulose powder with a particle size of 25 μm was dissolved in a mixed solution of 1-ethyl-3-methylimidazolium acetate and acetonitrile (volume ratio 4.4:1), with a cellulose powder mass fraction of 8%, to obtain a cellulose casting solution. The casting solution was then spin-coated using a spin coater at a speed of 300 rpm to obtain a cellulose membrane with a pore size of 0.45 μm and a membrane diameter of 13 mm. Simultaneously, 100 μL of membrane modification solution was dropped onto the center of the membrane. During the drop-in, a pipette with a 200 μL tip was used, with the tip 1 cm away from the membrane surface. After the drop-in was completed, the speed was kept constant. Finally, 3 mL of deionized water was dropped onto the membrane surface three times to rinse the membrane surface and remove residual organic solvents, glacial acetic acid, NaOH, etc. The membrane material was then dried at 25 °C for 40 min to obtain an uncrosslinked and uncured chitosan-crown ether polyimide modified cellulose membrane. The obtained cellulose membrane had a pore size of 415 nm and a porosity of 65%.

[0129] A dynamic cyclic adsorption experiment was conducted according to the method in Example 1. The maximum adsorption capacity of the modified cellulose membrane obtained in Comparative Example 3 for lithium ions was 13 mg / g, as determined by the dynamic cyclic adsorption experiment.

[0130] The comparison shows that when only chitosan, dibenzo-14-crown-4 polyimide and dibenzo-15-crown-5 polyimide are used to modify the membrane material, without using glutaraldehyde and NaOH solution to solidify the chitosan, the modified material is difficult to be efficiently fixed on the surface of the cellulose membrane material, thus making it difficult to improve the adsorption performance of the cellulose membrane material for lithium.

[0131] Interference ion experiment:

[0132] Using the membrane material from Example 2, five interference experiments were conducted to investigate the effects of coexisting ions on lithium ion adsorption by the membrane material, involving lithium / sodium, lithium / potassium, lithium / calcium, lithium / magnesium, and lithium / manganese. The concentration of each metal ion was 200 mg / L, and all metal ions used were metal chlorides. Dynamic adsorption experiments were performed, and the specific procedure is as follows:

[0133] The specific testing method for the dynamic cyclic adsorption experiment is as follows: The membrane is placed in a membrane cell with an effective diameter of 10 mm. A mixed solution prepared with lithium chloride and interfering ions is used. The flow rate is 2 L / min, and the membrane's effect on Li₂O₃ is studied over an operating time of 1 h. + The adsorption performance of Li was determined by ICP-OES. + The adsorption capacity of lithium ions and other metal ions can be obtained by measuring the concentration of other metal ions.

[0134] Tests showed that the chitosan-crown ether polyimide modified cellulose membrane of this invention adsorbed the following ions: lithium 35 mg / g, sodium 5.5 mg / g, potassium 6.2 mg / g, calcium 7.4 mg / g, magnesium 8.6 mg / g, and manganese 8.8 mg / g, exhibiting good selectivity.

[0135] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a chitosan-crown ether polyimide modified cellulose membrane, comprising the following steps: A membrane-modified solution is obtained by mixing crown ether polyimide, an organic solvent, and a chitosan solution. Cellulose casting solution was spin-coated into a film, and a film modification solution and glutaraldehyde were sequentially loaded during the film formation process to carry out a crosslinking reaction, thereby obtaining a chitosan-crown ether polyimide modified cellulose membrane precursor. NaOH solution was loaded onto the surface of the chitosan-crown ether polyimide modified cellulose membrane precursor and cured to obtain the chitosan-crown ether polyimide modified cellulose membrane. The crown ether polyimide includes one or more of dibenzo-12-crown-4 polyimide, dibenzo-14-crown-4 polyimide, dibenzo-15-crown-5 polyimide and dibenzo-18-crown-6 polyimide; The mass ratio of the crown ether polyimide to chitosan is 1:0.5~1.5; the mass ratio of the crown ether polyimide to the volume ratio of the organic solvent is 1 g:8~15 mL; The cellulose casting solution comprises cellulose powder and solvent, wherein the mass concentration of cellulose powder in the cellulose casting solution is 6-10%. The cellulose membrane obtained after the cellulose casting solution is used to form a film has a pore size of 0.25~0.45 µm; The volume ratio of the membrane modification solution to the cellulose casting solution is 0.2~0.5:

1.

2. The preparation method according to claim 1, characterized in that, The crown ether polyimide includes dibenzo-14-crown-4 polyimide and other crown ether polyimide materials, wherein the other crown ether polyimide materials include one of dibenzo-12-crown-4 polyimide, dibenzo-15-crown-5 polyimide and dibenzo-18-crown-6 polyimide; The mass ratio of the dibenzo-14-crown-4 polyimide to other crown ether polyimide materials is 1~3:

1.

3. The preparation method according to claim 1, characterized in that, The organic solvent includes a first solvent and a second solvent. The first solvent includes one of N,N'-dimethylformamide, N,N'-dimethylacetamide and N-methylpyrrolidone, and the second solvent includes acetone or acetonitrile.

4. The preparation method according to claim 1 or 3, characterized in that, The volume ratio of the membrane modification solution to glutaraldehyde is 50~200:20~50; The cross-linking reaction takes 3 to 10 minutes.

5. The preparation method according to claim 1, characterized in that, The concentration of the NaOH solution is 0.7~1.4 mol / L; The volume ratio of the membrane modification solution to the NaOH solution is 50~200:500~1000; The curing time is 10-15 minutes.

6. The chitosan-crown ether polyimide modified cellulose membrane prepared by the preparation method according to any one of claims 1 to 5 comprises a cellulose membrane and chitosan and crown ether polyimide loaded on the surface and internal pores of the cellulose membrane.

7. The chitosan-crown ether polyimide modified cellulose membrane according to claim 6, characterized in that, The chitosan-crown ether polyimide modified cellulose membrane has a specific surface area of ​​12~50 m². 2 / g.

8. The application of the chitosan-crown ether polyimide modified cellulose membrane according to claim 6 or 7 in the adsorption of lithium ions.

Citation Information

Patent Citations

  • A preparation method of dibenzo-14-crown-4 polyamide for lithium extraction from salt lakes

    CN116478396B

  • Crown ether modified chitosan nanofiber membrane as well as preparation method and application thereof

    CN112778553A

  • Crown ether polyimide nanofiber membrane as well as preparation method and application thereof

    CN117364342A

  • Nanofiltration membrane for extracting lithium from salt lake and preparation method of nanofiltration membrane

    CN117563440A